Graphene-doped spherical PbO2 anode and preparation method and application thereof
By growing a reduced TiO2 nanotube array on the surface of the titanium matrix and preparing a graphene-doped spherical PbO2 catalytic layer on it, the problems of low adhesion and easy shedding of Ti/PbO2 electrodes are solved, and the high stability and high electrocatalytic performance of the electrode are achieved, and As(III) and antibiotics can be effectively removed.
Patent Information
- Application Number
- CN202510178292.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-08
AI Technical Summary
Due to the structural differences between the substrate and the active layer, the existing Ti/PbO2 electrodes have problems such as low adhesion and easy shedding, which affects the electrocatalytic performance.
Reduced TiO2 nanotube array (RTNAs) intermediate layer was grown in situ on the surface of the titanium matrix, and a graphene-doped spherical PbO2 catalytic layer was prepared on the RTNAs intermediate layer by hydrothermal method to improve the conductivity and electrocatalytic properties of the electrodes.
It improves the stability and service life of the electrode, increases the electrochemically active surface area and electrocatalytic performance, can efficiently remove As(III) and antibiotics in groundwater, and reduces the toxicity of pollutants.
Smart Images

Figure CN119774718A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic oxidation, and in particular to a graphene-doped spherical PbO2 anode and a preparation method and application thereof. Background Art
[0002] At present, the pollution of water environment has attracted wide attention. The residual antibiotics in the environment mainly come from industrial production emissions, medical antibiotics and veterinary antibiotics. Cephalosporins belong to the β-lactam antibiotics, which have the characteristics of broad antibacterial spectrum, strong bactericidal ability, low toxicity and acid and alkali resistance. They are the most commonly used antibiotics, and their production and consumption account for about 60.0% of the total human antibiotic use. The absorption and utilization rate of cephalosporin antibiotics by humans or animals is very low. Most cephalosporins enter the water body with excrement, pollute surface water and groundwater, or enter the soil, and are absorbed by vegetables and crops, and then continue to accumulate in the human body through the food chain, threatening human health and the balance of the ecosystem. In addition, native high arsenic (As) groundwater is widely distributed around the world. Long-term drinking or contact with high arsenic groundwater can easily damage human liver, lungs, bladder, skin and other organs, and cause them to become cancerous, and can also lead to cardiovascular and nervous system diseases. The acceptable range of arsenic in water is 10μg / L. In groundwater, the form of arsenic is affected by the redox state in the water body. Among inorganic arsenic, As(III) is 60 times more toxic than As(V). As(III) exists mainly in the form of electrically neutral molecules (H3AsO3), which are more soluble and mobile in water. As(V) exists in the form of arsenate ions (AsO4 3- ) form, which is more easily adsorbed onto solid surfaces than As(III). Therefore, the removal of antibiotics and heavy metals in wastewater is imminent.
[0003] At present, oxidation is a commonly used treatment method in wastewater treatment. Common methods in the oxidation process include biological oxidation, chemical oxidation, photocatalytic oxidation and electrocatalytic oxidation. However, the biological oxidation method has a small scope of application and harsh reaction conditions; the chemical oxidation method requires the addition of an oxidant, which will lead to secondary pollution of the water body and the formation of toxic by-products; the photocatalytic oxidation method is mainly limited by the low light utilization efficiency, low quantum efficiency and poor adsorption capacity of photocatalysts such as TiO2. The focus of electrocatalytic oxidation technology (EO) is to use the transfer of electrons between electrode materials and solutions to reduce or remove pollutants by direct electrochemical reactions or indirect electrochemical conversions on the electrodes. EO has attracted widespread attention due to its advantages such as environmental protection, high efficiency, easy operation and diverse applications.
[0004] The high efficiency of EO mainly depends on the electrode material. Lead dioxide (PbO2) is widely used as an anode material due to its low cost, excellent electrocatalytic activity (high oxygen evolution potential, strong oxidation ability and conductivity), good corrosion resistance and other advantages. However, Ti / PbO2 electrodes have problems of low adhesion and easy detachment due to the structural differences between the substrate and the active layer. The active oxygen species generated during the electrochemical oxidation process diffuse inward and also cause the surface of the titanium substrate to passivate, affecting the electrocatalytic performance. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a graphene-doped spherical PbO2 anode and a preparation method and application thereof, in which a reduced TiO2 nanotube array (RTNAs) intermediate layer is in-situ grown on the surface of a titanium substrate to improve the conductivity of the anode and the stability of the electrode, and a graphene-doped spherical PbO2 catalytic layer is prepared on the RTNAs intermediate layer by a hydrothermal method to increase its electrochemically active surface area and electrocatalytic performance.
[0006] The present invention is achieved through the following technical solutions.
[0007] The first object of the present invention is to provide a method for preparing a graphene-doped spherical PbO2 anode, comprising the following steps: The Ti plate is polished, degreased and etched to form a pretreated Ti plate; the pretreated Ti plate is used as a working electrode and a stainless steel electrode is used as a counter electrode, and an amorphous TiO2 nanotube array electrode is obtained by oxidation at a constant potential in an electrolyte consisting of ethylene glycol, water and NH4F, and the process is as follows: 1) When a sufficient voltage is applied, the anodic oxidation reaction (Ti→Ti n+ + ne - 1. Start, 2. Ti n+ ions dissolve in the electrolyte and react with F - Reaction to form water-soluble TiF6 2- complex, 3) through dissolved Ti n+ Ions and O 2- (provided by H2O in the electrolyte) reacts to form a dense TiO2 layer, 4) Ti n+ Solvation and oxide formation compete to form nanotubes. After calcination, anatase TiO2 nanotube array electrode was obtained. Electrochemical reduction was performed in H2SO4 solution at constant current to prepare reduced TiO2 nanotube array electrode. The reduction process caused the color of TNAs to change from gray to black / blue. 4+ Partially reduced to Ti 3+ , while protons (H + )Embed( > Ti 4+ + e - + H + →> Ti 3+ H + ), generating oxygen vacancies (OVs) on its surface. These surface defects (i.e., Ti 3+ and OVs) can greatly improve the conductivity by redistributing extra electrons between Ti atoms and oxygen vacancies. H2SO4 can be replaced by Na2SO4 or (NH4)2SO4. The reduced TiO2 intermediate layer provided by the present invention is a uniformly arranged porous nanotube array structure with a diameter of about 100nm.
[0008] Lead acetate and surfactant are dissolved in alkaline solution. Surfactant is a structural directing agent for preparing spherical PbO2 and can adsorb the precursor Pb(OH)3 - The composite formed by the two can be used as a template for the formation of spherical PbO2. Potassium persulfate is added under vigorous stirring to form a uniform solution, and the reduced graphene oxide is added and ultrasonically dispersed to prepare a suspension; the prepared reduced TiO2 nanotube array electrode and the suspension are mixed for hydrothermal reaction, and potassium persulfate converts Pb(OH)3 - Oxidized to PbO2, and co-precipitated with reduced graphene oxide to prepare graphene-doped spherical PbO2 anode. NaOH can be replaced by KOH.
[0009] Preferably, in the electrolyte, the volume fraction ratio of ethylene glycol to water is 90:10 to 98:2, that is, the amount of ethylene glycol is 90% to 98% of the total volume of ethylene glycol and water, and the mass fraction of NH4F is 0.2% to 1%.
[0010] Preferably, during the electrochemical oxidation process, the constant potential is 40V to 50V, the oxidation time is 2h to 4h; the calcination temperature is 400°C to 500°C, and the calcination time is 100min to 150min.
[0011] Preferably, the concentration of H2SO4, Na2SO4 or (NH4)2SO4 solution is 0.05mol / L to 0.15mol / L, and the constant current density is 3mA / cm 2 ~8mA / cm 2 , electrochemical reduction for 5min to 15min.
[0012] Preferably, the mass of lead acetate is 10g / L to 15g / L, the surfactant is polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate or N-methylpyrrolidone, the mass of the surfactant is 5g / L to 8g / L, the alkaline solution is NaOH or KOH solution, the concentration of the alkaline solution is 0.5mol / L to 1.5mol / L, the mass of potassium persulfate is 9g / L to 13g / L, and the concentration of graphene is 0.1g / L to 0.5g / L.
[0013] Preferably, the hydrothermal reaction temperature is 80° C. to 100° C., and the hydrothermal reaction time is 45 min to 90 min.
[0014] Preferably, during pretreatment, the Ti plate is polished with sandpaper and then transferred to a boiling NaOH solution for degreasing and a boiling oxalic acid solution for etching to form a uniform rough surface. The mass fraction of NaOH is 3% to 8%, the mass fraction of oxalic acid is 8% to 12%, and the degreasing or etching time of the Ti plate is 1h to 4h.
[0015] Preferably, after the hydrothermal reaction, the electrode is naturally cooled to room temperature, and washed with anhydrous ethanol and deionized water. The electrode drying temperature is 50° C. to 70° C., and the drying time is 3 h to 5 h.
[0016] The second object of the present invention is to provide a graphene-doped spherical PbO2 anode prepared by the above preparation method.
[0017] The third object of the present invention is to provide the application of the above-mentioned graphene-doped spherical PbO2 anode in the electrocatalytic oxidation of As(III) or antibiotics, using the graphene-doped spherical PbO2 electrode as the anode, the stainless steel plate as the cathode, and a DC constant voltage power supply to electrocatalytically oxidize As(III) or cephalosporin antibiotics.
[0018] When used for electrocatalytic oxidation of As(III), the parameters are set as follows: current density is 30 mA / cm 2 ~70mA / cm 2 , the electrolyte Na2SO4 concentration is 0.01mol / L~0.50mol / L, the initial concentration of As(Ⅲ) is 5mg / L~20mg / L, and pH=3~11.
[0019] When used for electrocatalytic oxidation of antibiotics, the degradation parameters are set as follows: initial antibiotic concentration is 10 mg / L to 50 mg / L, current density is 30 mA / cm 2 ~75mA / cm 2 , pH=3~9, Na2SO4 concentration is 0.01mol / L~0.2mol / L.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention in-situ grows reduced TiO2 nanotube arrays (RTNAs) on the surface of a pretreated titanium substrate. The reduced TiO2 nanotube array intermediate layer formed by first oxidizing the Ti plate and then reducing it can accelerate electron transfer, increase the stability of the electrode, and improve the service life of the electrode. A graphene-doped spherical PbO2 catalyst layer is prepared on the RTNAs intermediate layer by a hydrothermal method. On the surface of the graphene-doped spherical PbO2, the spherical PbO2 is evenly distributed, the grains are closely connected and have a high coverage. Reduced graphene oxide (rGO) has the advantages of large surface area and good conductivity. The introduction of graphene can reduce the agglomeration of spherical PbO2, improve conductivity, provide more active sites for electrocatalytic oxidation, improve the mass transfer performance of the electrode, and increase its electrochemical active surface area and electrocatalytic performance by preparing the graphene-doped spherical PbO2 catalyst layer.
[0021] The preparation method of the invention is simple and environmentally friendly. The prepared anode material can be used to oxidize As(III) in groundwater into As(V), and can also degrade cephalosporin antibiotics, reduce the toxicity of pollutants, and has the advantage of high oxidation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 In the figure, a is a scanning electron microscope image of the reduced TiO2 nanotube array prepared in Example 1, b is a scanning electron microscope image of spherical PbO2, and c is a scanning electron microscope image of a graphene-doped spherical PbO2 electrode.
[0023] Figure 2 The influence of different factors on the oxidation of As(Ⅲ). Among them, a is the current density; b is the electrolyte concentration; c is the initial concentration of As(Ⅲ); d is pH.
[0024] Figure 3 The effects of different factors on the degradation of cefuroxime. a is the initial concentration of cefuroxime; b is the current density; c is the pH; d is the electrolyte concentration.
[0025] Figure 4 is the OH generation capacity of different electrodes.
[0026] Figure 5 Effect of different electrodes on electrocatalytic oxidation of As(Ⅲ). DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0028] Ti / PbO2 electrodes have problems of low adhesion and easy detachment due to the structural differences between the substrate and the active layer. The active oxygen species generated during the electrochemical oxidation process diffuse inward and also cause the surface of the titanium substrate to be passivated. Therefore, the present invention in situ grows reduced TiO2 nanotube arrays (RTNAs) on the surface of the titanium substrate to improve the conductivity of the anode and the stability of the electrode. In addition, existing research work mainly prepares PbO2 anodes by electrodeposition methods, and investigates the effects of deposition conditions on the composition and properties of PbO2 coatings including doping layers and composite layers. However, PbO2 electrodes prepared by traditional processes are usually energy-intensive and pyramidal structures, with limited electrochemical active surface areas and electron competition for side reactions such as oxygen evolution. Increasing the specific surface area of the catalytic layer can be achieved by changing the crystal structure and chemical composition of the catalytic layer to give it a specific microscopic multidimensional structure, such as tubular, spherical, mesoporous electrodes, etc. Reduced graphene oxide (rGO) has the advantages of large surface area and good conductivity, and can improve the mass transfer performance of the electrode. Therefore, the present invention prepares a graphene-doped spherical PbO2 catalyst layer on the RTNAs intermediate layer by a hydrothermal method to increase its electrochemically active surface area and electrocatalytic performance.
[0029] Specifically, the present invention provides a method for preparing a graphene-doped spherical PbO2 anode, comprising the following steps: S1. Preparation of reduced TiO2 nanotube array: After polishing the Ti plate with sandpaper, transfer it to boiling NaOH solution for degreasing and boiling oxalic acid solution for etching to form a uniform rough surface. The pretreated Ti plate is used as the working electrode, and the stainless steel electrode of the same area is used as the counter electrode. In an electrolyte composed of ethylene glycol, water and NH4F, an amorphous TiO2 nanotube array electrode is obtained by oxidation at constant potential. After calcination, it is electrochemically reduced in H2SO4 solution at constant current.
[0030] S2. Preparation of graphene-doped spherical PbO2 electrodes: Lead acetate and surfactant were dissolved in an alkaline solution. The surfactant was used as a structure-directing agent to adsorb the precursor Pb(OH)3 - The formed complex is used as a template for the formation of spherical PbO2. Potassium persulfate is added under vigorous stirring to form a uniform solution. After the reduced graphene oxide is added and ultrasonically dispersed uniformly, the prepared reduced TiO2 nanotube array electrode and the above suspension are transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and heated, and potassium persulfate converts the Pb(OH)3 in the template into - Oxidized to PbO2, and co-precipitated with reduced graphene oxide on the reduced TiO2 nanotube array electrode to prepare a graphene-doped spherical PbO2 anode. After the reaction is completed, it is naturally cooled to room temperature, and the electrode is washed with anhydrous ethanol and deionized water, and dried for use.
[0031] The present invention prepares a graphene-doped spherical PbO2 anode by an electro-oxidation / reduction method and a hydrothermal reaction method. The electrode preparation method is simple and green. The reduced TiO2 nanotube array intermediate layer formed by first oxidizing the Ti plate and then reducing it can accelerate electron transfer, increase the stability of the electrode, and improve the service life of the electrode. The reduced TiO2 intermediate layer provided by the present invention is a uniformly arranged porous nanotube array structure with a diameter of about 100nm. The spherical PbO2 on the surface of the graphene-doped spherical PbO2 anode is evenly distributed, the grains are closely connected and have a high coverage, and the introduction of graphene can reduce the agglomeration of spherical PbO2, improve conductivity, and provide more active sites for electrocatalytic oxidation. It can be used to oxidize As(III) in groundwater into As(V), and can also degrade cephalosporin antibiotics, reduce the toxicity of pollutants, and has the advantages of high oxidation efficiency.
[0032] The present invention is specifically described below by means of the following examples and comparative examples.
[0033] Example 1 A method for preparing a graphene-doped spherical PbO2 anode comprises the following steps: S1. Preparation of reduced TiO2 nanotubes: After polishing the Ti plate with sandpaper, transfer it to a boiling 5% NaOH solution for degreasing for 2 hours and a boiling 10% oxalic acid solution for etching for 3 hours to form a uniform rough surface. The pretreated Ti plate was used as the working electrode and the stainless steel plate was used as the cathode. It was placed in an electrolyte consisting of ethylene glycol, water and NH4F for oxidation under constant potential. The volume fraction ratio (v / v) of ethylene glycol and water was 95:5, the mass fraction of NH4F was 0.5%, the constant potential was 45V, and the oxidation time was 3 hours. After oxidation, it was placed in a muffle furnace and calcined at 450℃ for 120 minutes for annealing. After taking it out, it was rinsed with deionized water to obtain an amorphous TiO2 nanotube array electrode. The prepared TiO2 nanotube electrode was used as the cathode and the stainless steel plate of the same area was used as the anode. In a 0.1M H2SO4 solution, the constant current density was 5mA / cm 2 The reduced TiO2 nanotube array electrode was obtained by electrochemical reduction for 10 min.
[0034] S2. Preparation of graphene-doped spherical PbO2 electrodes: 2.5 g of lead acetate and 1.2 g of polyvinyl pyrrolidone were dissolved in 200 mL of 1 M NaOH solution, 2.2 g of potassium persulfate was added under vigorous stirring to form a uniform solution, 0.06 g of reduced graphene oxide was added and ultrasonically dispersed uniformly, and the prepared reduced TiO2 nanotube array electrode and the above suspension were transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and heated at 90 ° C for 60 min, cooled naturally to room temperature, and the electrode was washed with anhydrous ethanol and deionized water, placed in an oven at 50 ° C for 4 h, and used for standby. The prepared electrode is represented by RTNAs / rGO-spherical PbO2.
[0035] Figure 1 This is a scanning electron microscope image (SEM) of the graphene-doped spherical PbO2 anode prepared in Example 1. Figure 1 Figure a shows that a uniformly arranged reduced TiO2 nanotube array is grown in situ on a Ti plate, with a pore size of about 100 nm. Figure 1 As can be seen in Figure b, after hydrothermal treatment, spherical PbO2 crystals are dispersed and deposited on the reduced TiO2 nanotube array layer. After rGO is doped into the PbO2 coating, the number of spherical PbO2 structures on the electrode surface increases and the structure is dense. rGO and spherical PbO2 are tightly bound ( Figure 1 (c) can provide more active sites for electrocatalytic oxidation, prevent direct contact between the electrolyte and the intermediate layer, and greatly improve the electrode life and electrode catalytic effect.
[0036] Example 2 A method for preparing a graphene-doped spherical PbO2 anode comprises the following steps: S1. Preparation of reduced TiO2 nanotubes: After polishing the Ti plate with sandpaper, transfer it to a boiling 3% NaOH solution for degreasing for 2.5h and a boiling 8% oxalic acid solution for etching for 4h to form a uniform rough surface. The pretreated Ti plate was used as the working electrode and the stainless steel plate was used as the cathode. It was placed in an electrolyte consisting of ethylene glycol, water and NH4F for oxidation under constant potential. The volume fraction ratio (v / v) of ethylene glycol and water was 97:3, the mass fraction of NH4F was 0.3%, the constant potential was 42V, and the oxidation time was 4h. After oxidation, it was placed in a muffle furnace and calcined at 400℃ for 150min, annealed, and rinsed with deionized water after being taken out to obtain an amorphous TiO2 nanotube array electrode. The prepared TiO2 nanotube electrode was used as the cathode and the stainless steel plate of the same area was used as the anode. In a 0.05M H2SO4 solution, the constant current density was 5mA / cm 2 The reduced TiO2 nanotube array electrode was obtained by electrochemical reduction for 15 min.
[0037] S2. Preparation of graphene-doped spherical PbO2 electrode: 3 g of lead acetate and 1.5 g of sodium dodecylbenzene sulfonate were dissolved in 200 mL of 1.5 M NaOH solution, 2 g of potassium persulfate was added under vigorous stirring to form a uniform solution, 0.1 g of reduced graphene oxide was added and ultrasonically dispersed uniformly, and the prepared reduced TiO2 nanotube array electrode and the above suspension were transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and heated at 100 ° C for 45 min, cooled naturally to room temperature, and the electrode was washed with anhydrous ethanol and deionized water, and dried in an oven at 50 ° C for 5 h for use.
[0038] The surface of the obtained spherical PbO2 electrode is relatively rough, with smaller agglomerates and more irregular micropores, and good coverage.
[0039] Example 3 A method for preparing a graphene-doped spherical PbO2 anode comprises the following steps: S1. Preparation of reduced TiO2 nanotubes: After polishing the Ti plate with sandpaper, transfer it to a boiling 8% NaOH solution for degreasing for 1.5h and a boiling 12% oxalic acid solution for etching for 2h to form a uniform rough surface. The pretreated Ti plate was used as the working electrode and the stainless steel plate was used as the cathode. It was placed in an electrolyte consisting of ethylene glycol, water and NH4F for oxidation under constant potential. The volume fraction ratio (v / v) of ethylene glycol and water was 90:10, the mass fraction of NH4F was 0.8%, the constant potential was 50V, and the oxidation time was 2h. After oxidation, it was placed in a muffle furnace and calcined at 500℃ for 100min, annealed, and rinsed with deionized water after being taken out to obtain an amorphous TiO2 nanotube array electrode. The prepared TiO2 nanotube electrode was used as the cathode and the stainless steel plate of the same area was used as the anode. In a 0.15M H2SO4 solution, the constant current density was 3mA / cm 2 The reduced TiO2 nanotube array electrode was obtained by electrochemical reduction for 15 min.
[0040] S2. Preparation of graphene-doped spherical PbO2 electrode: 2g of lead acetate and 1g of N-methylpyrrolidone were dissolved in 200mL of 0.5M NaOH solution, 1.8g of potassium persulfate was added under vigorous stirring to form a uniform solution, 0.02g of reduced graphene oxide was added and ultrasonically dispersed uniformly, and the prepared reduced TiO2 nanotube array electrode and the above suspension were transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and heated at 80°C for 90min, cooled naturally to room temperature, and the electrode was washed with anhydrous ethanol and deionized water, and dried in an oven at 60°C for 4h for use.
[0041] The obtained spherical PbO2 electrode has good coverage and basically no holes, and rGO is evenly distributed in the PbO2 spherical structure.
[0042] Study on the Electrocatalytic Oxidation Performance of Graphene-doped Spherical PbO2 Anode for As(Ⅲ) The graphene-doped spherical PbO2 electrode prepared in Example 1 was used as the anode, the stainless steel plate was used as the cathode, the electrode spacing was 1.5 cm, and a DC constant voltage power supply was connected for oxidation; the electrolyte was Na2SO4, and the effects of different factors on the electrocatalytic oxidation of As(III) were investigated.
[0043] The graphene-doped spherical PbO2 anode prepared in Example 1 electrocatalytically oxidizes As(III). Figure 2 As shown in a, at 60 min, 30 and 40 mA / cm 2 The oxidation rates of As(Ⅲ) were 87.23% and 95.06% at current densities of 50, 60 and 70 mA / cm 2 The oxidation rate of As(Ⅲ) reached 100% under all current densities. Within a certain range, with the increase of current density, the oxidation rate of As(Ⅲ) gradually increased, which was because higher current density promoted the generation of ·OH and enhanced the electrocatalytic oxidation ability of the electrode.
[0044] The electrolyte concentration can directly affect the conductivity during the oxidation process. Figure 2 As shown in Figure b, when the Na2SO4 concentration is 0.01, 0.05, 0.1, 0.2 and 0.5 mol / L, the oxidation rates of As(Ⅲ) after 60 min of oxidation are 58.23, 68.88, 99.46, 99.25 and 99.56%, respectively. Within a certain range, the oxidation rate of As(Ⅲ) increases with the increase of electrolyte concentration. This may be because the increase in Na2SO4 concentration increases the ionic strength and conductivity of the solution, which helps the formation of H2O2 and ·OH and promotes the oxidation of As(Ⅲ). However, excessive SO4 2- Can remove OH to produce S2O8 - Moreover, sulfate will form a salt film on the anode surface, consuming the active sites on the anode surface and preventing pollutants from migrating to the electrode surface.
[0045] like Figure 2As shown in Figure c, when the As(Ⅲ) concentration increased from 5 mg / L to 20 mg / L, the oxidation rates of As(Ⅲ) reached 100.00%, 86.57% and 63.80% respectively after 40 minutes of electrolysis. As the initial concentration increases, the oxidation rate of As(Ⅲ) decreases. This is because under the same experimental conditions, the amount of oxidant produced is constant, and when the initial concentration is low, As(Ⅲ) is more easily attacked by the oxidant. In addition, As(Ⅲ) is mainly in the form of neutral charge, mainly in the form of arsenite (H3AsO3), while As(V) is usually in the form of negatively charged arsenate anions (H2AsO4 - ). In high concentration solutions, As(V) generated by the electrocatalytic oxidation process is more easily adsorbed on the anode surface, thereby reducing the generation of oxidants, preventing As(III) from contacting the active sites of the anode, and reducing the electrocatalytic oxidation of pollutants by the anode.
[0046] Figure 2 The effect of initial pH on the As(Ⅲ) oxidation rate was studied in Figure d. When the initial pH increased from 3 to 11, the As(Ⅲ) oxidation rate reached 100.00% after 60 min, indicating that the graphene-doped spherical PbO2 anode has a good electrocatalytic oxidation effect on As(Ⅲ) in a wide pH range. This may be because under acidic conditions, H + It will inhibit the decomposition and oxygen evolution reaction of OH, thereby increasing the oxidation rate of pollutants. - It may be converted to OH under electrocatalytic reaction, which can also improve the oxidation of pollutants to a certain extent. However, under alkaline conditions, the oxygen evolution reaction will increase, and more energy consumption may be required to increase the oxidation of pollutants.
[0047] In addition, the graphene-doped spherical PbO2 anode prepared in Example 1 can also electrocatalytically degrade cefuroxime. Figure 3 As shown in a, when the concentration of cefuroxime acid is 10 mg / L, its removal rate reaches 100% after 40 minutes. When the initial concentration of cefuroxime acid is 20 mg / L, 30 mg / L, 40 mg / L and 50 mg / L, the removal rates after 90 minutes of degradation are 100%, 100%, 99.34% and 97.28%, respectively. As above, with the increase of initial concentration, the catalytic degradation rate of the electrode shows a downward trend. This is because the electrocatalytic oxidation reaction mainly relies on the electron transfer at the anode and the subsequent generation of ·OH with high redox potential to oxidize cefuroxime. When the area of the anode plate is constant, a high concentration of cefuroxime will cause the catalytic oxidation reaction to be incomplete, resulting in more intermediates accumulating on the electrode surface, hindering the contact between cefuroxime acid and the active sites on the catalytic anode, thereby affecting the formation of ·OH and reducing the degradation rate of cefuroxime.
[0048] Depend on Figure 3As can be seen in b, at 30mA / cm 2 , 45mA / cm 2 、60mA / cm 2 , 75mA / cm 2 At the current density of 30~60mA / cm, the removal rates of cefuroxime were 94.81%, 95.81%, 99.34% and 97.50% respectively. 2 In the range of 75 mA / cm2, the removal rate of cefuroxime increased with the increase of current density, which may be due to the increase in the number of transferable electrons and hydroxyl radicals in the system, thereby accelerating the electrochemical reaction rate. 2 Under the current density, the removal rate of cefuroxime decreased. It may be that at a higher current density, too many oxides or free radicals were generated on the electrode surface, leading to side reactions or competitive reactions.
[0049] Depend on Figure 3 It can be seen from Figure c that when the pH is 3, 5, 7, and 9, the removal rates of cefuroxime are 95.93%, 99.34%, 94.15%, and 97.09%, respectively. Under neutral conditions, the removal rate of cefuroxime is the lowest, because the structure of cephalosporin antibiotics is stable under neutral conditions, and the rate at which hydroxyl radicals destroy their chemical structure is lower than that in a weak acid and weak base environment. Acidic conditions can inhibit the oxygen evolution reaction during the reaction process, increase the yield and utilization of hydroxyl radicals, and thus improve the performance of electrode electrocatalytic oxidation. Under alkaline conditions, hydroxyl radicals are more likely to generate oxidants, which indirectly oxidize antibiotics, resulting in a reduction in hydroxyl radicals that directly react with cefuroxime, which to a certain extent weakens the degradation effect of cefuroxime acid.
[0050] It can be seen from Figure 3d that when the Na2SO4 electrolyte concentration is 0.01mol / L, 0.05mol / L, 0.1mol / L and 0.2mol / L, the cefuroxime removal rates after 90min of degradation are 85.21%, 95.48%, 99.34% and 100%, respectively. With the increase of the electrolyte Na2SO4 concentration, the removal rate of cefuroxime acid also shows a gradual increase. The reason may be that the increase of electrolyte concentration can reduce resistance, improve conductivity, reduce energy consumption, and thus improve the electrocatalytic oxidation performance.
[0051] Comparative Example 1 PbO2 electrode prepared by traditional process. The specific preparation method is: using Ti plate as anode and stainless steel plate as cathode, constant current electrodeposition is performed, and the PbO2 electroplating solution composition is: 0.1mol / L HNO3, 200g / L Pb(NO3)2, 0.5g / L NaF. Electroplating conditions: 65℃, 200A / m 2, forward and reverse electroplating for 30 minutes, keep stirring during electrodeposition, and clean the metal Pb precipitated at the cathode in time. After the electrodeposition is completed, the electrode surface is ultrasonically cleaned in pure water, and the Ti / PbO2 electrode is obtained after drying.
[0052] Lead nitrate used in the preparation of PbO2 electrodes by traditional processes is corrosive and highly toxic. The preparation process consumes a lot of electricity. The prepared electrodes are usually energy-intensive and pyramidal in structure. The electrochemically active surface area is limited, and there is electron competition for side reactions such as oxygen evolution. The present invention prepares a graphene-doped spherical PbO2 catalyst layer by a hydrothermal method, and uses lead acetate with low toxicity. The hydrothermal method is simple and easy to operate, and the high specific surface area of spherical PbO2 helps to improve the catalytic activity. The conductivity of the anode and the stability of the electrode are improved by in-situ growth of reduced TiO2 nanotube arrays (RTNAs) on the surface of the titanium substrate. Combined with reduced graphene oxide (rGO), it has the advantages of large surface area and good conductivity, and further improves the mass transfer performance of the electrode.
[0053] Comparative Example 2 Preparation of Ti / spherical PbO2 electrode: S1. After polishing the Ti plate with sandpaper, transfer it to a boiling 5% NaOH solution for degreasing for 2 hours and a boiling 10% oxalic acid solution for etching for 3 hours to form a uniform rough surface, thereby obtaining a pretreated Ti plate.
[0054] S2. Dissolve 2.5 g of lead acetate and 1.2 g of polyvinyl pyrrolidone in 200 mL of 1 M NaOH solution, add 2.2 g of potassium persulfate under vigorous stirring to form a uniform solution, transfer the prepared pretreated Ti plate and the above solution to a hydrothermal reactor lined with polytetrafluoroethylene, seal and heat at 90 ° C for 60 min, cool naturally to room temperature, wash the electrode with anhydrous ethanol and deionized water, and place it in an oven at 50 ° C for 4 h for use.
[0055] Comparative Example 3 Preparation of TNAs / spherical PbO2 electrodes: S1. After polishing the Ti plate with sandpaper, transfer it to a boiling 5% NaOH solution for degreasing for 2 hours, and then etch it in a boiling 10% oxalic acid solution for 3 hours to form a uniform rough surface. The pretreated Ti plate is used as the working electrode and the stainless steel plate is used as the cathode. It is placed in an electrolyte composed of ethylene glycol, water and NH4F for oxidation under constant potential. The volume fraction ratio (v / v) of ethylene glycol and water is 95:5, the mass fraction of NH4F is 0.5%, the constant potential is 45V, and the oxidation time is 3 hours. After oxidation, it is placed in a muffle furnace and calcined at 450℃ for 120 minutes for annealing. After taking it out, it is rinsed with deionized water to obtain an amorphous TiO2 nanotube array electrode.
[0056] S2. Dissolve 2.5 g of lead acetate and 1.2 g of polyvinyl pyrrolidone in 200 mL of 1 M NaOH solution, add 2.2 g of potassium persulfate under vigorous stirring to form a uniform solution, transfer the prepared amorphous TiO2 nanotube array electrode and the above solution to a hydrothermal reactor lined with polytetrafluoroethylene, seal and heat at 90°C for 60 min, cool naturally to room temperature, wash the electrode with anhydrous ethanol and deionized water, and dry it in an oven at 50°C for 4 h for use.
[0057] Comparative Example 4 Preparation of RTNAs / spherical PbO2 electrodes: S1. After polishing the Ti plate with sandpaper, transfer it to a boiling 5% NaOH solution for degreasing for 2 hours, and then etch it in a boiling 10% oxalic acid solution for 3 hours to form a uniform rough surface. The pretreated Ti plate was used as the working electrode and the stainless steel plate was used as the cathode. It was placed in an electrolyte consisting of ethylene glycol, water and NH4F for oxidation under constant potential. The volume fraction ratio (v / v) of ethylene glycol and water was 95:5, the mass fraction of NH4F was 0.5%, the constant potential was 45V, and the oxidation time was 3 hours. After oxidation, it was placed in a muffle furnace and calcined at 450℃ for 120 minutes, annealed, and rinsed with deionized water after being taken out to obtain an amorphous TiO2 nanotube array electrode. The prepared TiO2 nanotube electrode was used as the cathode and the stainless steel plate of the same area was used as the anode. In a 0.1M H2SO4 solution, the constant current density was 5mA / cm 2 The reduced TiO2 nanotube array electrode was obtained by electrochemical reduction for 10 min.
[0058] S2. Dissolve 2.5 g of lead acetate and 1.2 g of polyvinyl pyrrolidone in 200 mL of 1 M NaOH solution, add 2.2 g of potassium persulfate under vigorous stirring to form a uniform solution, transfer the prepared reduced TiO2 nanotube array electrode and the above solution to a hydrothermal reactor lined with polytetrafluoroethylene, seal and heat at 90°C for 60 min, cool naturally to room temperature, wash the electrode with anhydrous ethanol and deionized water, dry it in an oven at 50°C for 4 h, and set aside.
[0059] Comparison of the production capacity of ·OH of different electrodes. ·OH plays a key role in the oxidation process of pollutants, and its production rate can be used as an important indicator for electrode evaluation. The experiment uses salicylic acid as a capture agent to test the production capacity of ·OH of four different electrodes prepared in Example 1 and Comparative Examples 2 to 4. Figure 4As shown in Figure 2, the ·OH production of Ti / spherical PbO2, TNAs / spherical PbO2, RTNAs / spherical PbO2 and RTNAs / rGO-spherical PbO2 electrodes increased with time, and the production at 30 min was 14.35, 17.13, 35.2, and 38.06 mM / (min·m 2 ), the ·OH production of RTNAs / rGO-spherical PbO2 electrode is 2.65 times that of Ti / spherical PbO2, which significantly increases the production of ·OH. The increase in the ·OH production rate may be due to the introduction of intermediate layer RTNAs and the doping of reduced graphene oxide carbon materials, which makes the electrode surface particles rougher and more dispersed, inhibits the occurrence of oxygen evolution side reaction, improves the electrode current efficiency, and improves the ability of the electrode to produce active oxygen.
[0060] Comparison of the electrocatalytic oxidation effects of the above four different electrodes on As(Ⅲ).
[0061] The electrocatalytic oxidation of As(III) further demonstrated that the introduction of interlayer RTNAs and the doping of reduced graphene oxide indeed improved the oxidation efficiency of As(III). Figure 5 As shown in the figure, after 60 min of electrolysis, the electrocatalytic oxidation rates of As(Ⅲ) by Ti / spherical PbO2, TNAs / spherical PbO2, RTNAs / spherical PbO2 and RTNAs / rGO-spherical PbO2 anodes were 31.12%, 43.32%, 74.72% and 100.00%, respectively, and the oxidation rate of As(Ⅲ) by RTNAs / rGO-spherical PbO2 electrode was the highest. The results show that the nanotube structure not only enhances electron transfer but also provides more catalytic active sites. After rGO is doped into the active layer of PbO2 spheres, the electrochemical oxidation performance of the electrode is increased, the formation of ·OH is promoted, and the electrocatalytic oxidation of pollutants is accelerated.
[0062] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a graphene-doped spherical PbO2 anode, characterized in that: The following steps are involved: The Ti plate is pretreated, and the pretreated Ti plate is used as a working electrode, and anodized in an electrolyte to prepare an amorphous TiO2 nanotube array electrode, and after calcination, electrochemical reduction is performed by constant current to prepare a reduced TiO2 nanotube array electrode; Lead acetate and surfactant were dissolved in alkaline solution, and the surfactant was used as a structure-directing agent to adsorb the precursor Pb(OH)3 - The formed complex is used as a template for the spherical PbO2, potassium persulfate is added under stirring to form a uniform solution, and reduced graphene oxide is added and ultrasonically dispersed to prepare a suspension; the prepared reduced TiO2 nanotube array electrode and the suspension are mixed for hydrothermal reaction, and potassium persulfate converts Pb(OH)3 in the template under alkaline conditions. - Oxidized to PbO2, PbO2 and reduced graphene oxide were co-precipitated on the reduced TiO2 nanotube array electrode to prepare graphene-doped spherical PbO2 anode.
2. The preparation method according to claim 1, characterized in that: The surfactant is polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate or N-methyl pyrrolidone, the mass concentration of the surfactant is 5g / L-8g / L, the mass concentration of lead acetate is 10g / L-15g / L, the alkaline solution is NaOH or KOH solution, the concentration of the alkaline solution is 0.5mol / L-1.5mol / L, the mass concentration of potassium persulfate is 9g / L-13g / L, and the concentration of reduced graphene oxide is 0.1g / L-0.5g / L.
3. The preparation method according to claim 1, characterized in that: The hydrothermal reaction temperature is 80°C to 100°C, and the hydrothermal reaction time is 45min to 90min.
4. The preparation method according to claim 1, characterized in that: The electrolyte is composed of ethylene glycol, water and NH4F, wherein the mass fraction of NH4F is 0.2% to 1%, and the amount of ethylene glycol is 90% to 98% of the total volume of ethylene glycol and water.
5. The preparation method according to claim 1, characterized in that: During the anodizing process, the stainless steel electrode is the counter electrode, the constant potential is 40V to 50V, and the oxidation time is 2h to 4h; the calcination temperature is 400°C to 500°C, and the calcination time is 100min to 150min.
6. The preparation method according to claim 1, characterized in that: In the electrochemical reduction step, the calcined electrode is electrochemically reduced in a H2SO4, Na2SO4 or (NH4)2SO4 solution, the concentration of the H2SO4, Na2SO4 or (NH4)2SO4 solution is 0.05mol / L to 0.15mol / L, and the constant current density is 3mA / cm 2 ~8mA / cm 2 , electrochemical reduction for 5min to 15min.
7. A graphene-doped spherical PbO2 anode prepared according to the preparation method according to any one of claims 1 to 6.
8. The use of the graphene-doped spherical PbO2 anode according to claim 7 in electrocatalytic oxidation of As(III) or antibiotics, characterized in that: The graphene-doped spherical PbO2 anode described in claim 7 is used as the anode, the stainless steel plate is used as the cathode, and a DC constant voltage power supply is used to electrocatalytically oxidize As(III) or antibiotics.
9. The use according to claim 8, characterized in that: When used for electrocatalytic oxidation of As(III), the parameters are set as follows: current density is 30 mA / cm 2 ~70mA / cm 2 , the electrolyte Na2SO4 concentration is 0.01mol / L~0.50mol / L, the initial concentration of As(Ⅲ) is 5mg / L~20mg / L, and pH=3~11.
10. The use according to claim 8, characterized in that: When used for electrocatalytic oxidation of antibiotics, the parameters are set as follows: initial antibiotic concentration is 10 mg / L to 50 mg / L, current density is 30 mA / cm 2 ~75mA / cm 2 , pH=3~9, electrolyte Na2SO4 concentration is 0.01mol / L~0.2mol / L.
Citation Information
Patent Citations
Method for preparing PbO2-modified TiO2 nanotube electrode
CN102534718A
Composite photocatalyst, its preparation and application
CN102962080A
Method for preparing titanium dioxide nanotube array photoelectrode
CN103361689A
Titanium / graphene / oxide combined electrode
CN103526235A
Preparation method for carbon nanotube and / or graphene reinforced lead based composite anode
CN104131318A
Cited By
Preparation method and application of nickel-doped lead dioxide ozone catalytic anode
CN120573809A